Dexamethasone Regulates Cochlear Expression of Deafness-associated Proteins Myelin Protein Zero and Heat Shock Protein 70, as Revealed by iTRAQ Proteomics. Issue 7 (August 2015) - Maeda, Yukihide; Fukushima, Kunihiro; Kariya, Shin; Orita, Yorihisa; Nishizaki, Kazunori
Abstract : Aim: Using proteomics, we aimed to identify the proteins differentially regulated by dexamethasone in the mouse cochlea based on mass-spectrometry data. Background: Glucocorticoid therapy is widely used for many forms of sensorineural hearing loss; however, the molecular mechanism of its action in the cochlea remains poorly understood. Methods: Dexamethasone or control saline was intratympanically applied to the cochleae of mice. Twelve hours after application, proteins differentially regulated by dexamethasone in the cochlea were analyzed by isobaric Tag for Relative and Absolute Quantitation (iTRAQ)–mass spectrometry. Next, dexamethasone-dependent regulation of these proteins was verified in the cochleae of mice with noise-induced hearing loss (NIHL) and systemic administration of dexamethasone by western blotting. Immunolocalizations of these proteins were examined in cochleae with NIHL. Results: A total of 247 proteins with a greater than 95% confidence interval of protein identification were found, and 11 differentially expressed proteins by dexamethasone were identified by the iTRAQ–mass spectrometry. One protein, myelin protein zero (Mpz), was upregulated (1.870 ± 0.201-fold change, p < 0.01) at 6 hours post-systemic dexamethasone and noise exposure in a mouse model of NIHL. Heat shock protein 70 (Hsp70) was downregulated (0.511 ± 0.274-fold change, p < 0.05) at 12 hours post-systemic dexamethasone. Immunohistochemistry confirmed Mpz localization to the efferent and afferent processes of the spiral neurons, whereas Hsp70 showed a more ubiquitous expression pattern in the cochlea. Conclusion: Both Mpz and Hsp70 have been reported to be closely associated with sensorineural hearing loss in humans. Dexamethasone significantly modulated the expression levels of these proteins in the cochleae of mice. Abstract : Supplemental digital content is available in the text.